Perlindungan Hukum Bagi Pemegang Saham Minoritas dalam Kasus Sengketa Perusahan - Wahyudi Wahyudi; Muhammad Tauvic Annur; Nuri Safitri; Sakirah Sakirah (al-Battar: Jurnal Pamungkas Hukum, 2025)
Legal protection for minority shareholders in corporate disputes is a crucial aspect in maintaining the principles of fairness and balance in corporate governance. Minority shareholders are often in an unbalanced position due to the dominance of majority shareholders in strategic decision-making. This study aims to analyze the forms of legal protection available to minority shareholders in Indonesia and evaluate the effectiveness of their implementation. The research method used is normative juridical with a legislative approach, literature study, and case analysis. The results of the study show that there are two main forms of legal protection, namely preventive (through the right to information, the right to vote in the GMS, and the right to object) and repressive (through the right to sue, arbitration mechanism, and mediation). However, the effectiveness of this protection is still constrained by the dominance of majority shareholders, limited access to information, and low legal awareness among minority shareholders. The discussion in this article highlights the need to strengthen regulations, increase corporate transparency, legal education, and optimize non-litigation dispute resolution to create a fairer and more functional legal protection system for minority shareholders.